Promoción y desarrollo humano : su relación actual con el trabajo social en salud (2007)
ABSTRACT: In this article, social work’s intervention in health area is dimensioned from promotion, which is considered as a social practice that unleashes self-management processes on communities to participate in an active way in their social development. In this sense, the social work professional’s role is emphasized as the one who has to lead communitary organization and participation, through collective projects encouragement that carry to health maintenance in subjects and, in a general way, elements whit which human development contributes to health promotion are insinuated and a relation with intervention from social work in present time is tried to established.